In Hindsight: An Essay Concerning My Limited Moral Understanding - Forsberg, Anders Niklas (Springer Nature Switzerland AG, 2024)
This article explores one central assumption that is guiding large portions of contemporary (analytic) moral philosophy: the idea that moral philosophy has to be forward-looking and action-guiding. By paying attention to a number of examples, it is argued that this guiding assumption flies in the face of important aspects of actual moral life. Moral situations are not (always) of the nature that we can plan for them, and reason about them in advance. Rather, the moral reality, or the moral contexts, are often such that the moral situation is created in the scene, and hence something that is only available to reflect upon in hindsight. There are, at least, two central reasons why this is so: The first is that the sense, meaning, of the actions and the concepts we use in reflection about them, are not locked beforehand, and our understanding of them are formed in the process. The second reason is that moral situations come about in a responsive, rather than planned, way. That is, we discover our moral world by means of our reactive interactions, rather than in theoretical reflection that aims to produce ""anticipated beliefs."" Thus, this article suggests a way of exploring morality's backward-looking nature that does not misrepresent moral reality."
Zpětný pohled: Eseje o mém omezeném morálním chápání
Keywords: Action-guidance; Hindsight; Raimond Gaita; Moral theory; Realism; Virtue ethics; Raimond Gaita; teorie morálky; realismus; etika ctnosti; zpětný pohled; vedení k jednání